South-facing Jangha (wall) of Neelkanth Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
A closer view of the south-facing jangha (wall) of the central shrine of the Neelkanth Mahadev Temple. The jangha is profusely carved with sculptures. The central bhadra (central projection) has a ferocious depiction of Shiva, and the intermediate and corner projections have ascetic, surasundaris (celestial damsels), and dikpalas (deities for cardinal directions). The recesses just flanking the central shrine have vyalas (composite mythical creatures).